A comparison between heat transfer correlations obtained from experimental data and numerical simulation of flow of stirred yoghurt during cooling in plate heat exchangers - Afonso, Isabel M. (2004)
Thermal processing is widely used in the food industry mainly to improve quality and safety of food products. The investigation of heat transfer problems of non-Newtonian fluids during heating and cooling in heat exchangers is of major interest since the main factor limiting heat transfer is the viscous behaviour of these fluids. Therefore, the knowledge of the interface heat transfer coefficients is important in the design of food processes and processing equipment. In the present work, simulations of stirred yoghurt cooling in a plate heat exchanger were performed using computational fluid dynamics (CFD) calculations and the obtained results were compared with experimental data. Simulations were carried out using the commercial finite element method package POLYFLOW, being the geometrical domain the representation of a single 3D channel of the plate heat exchanger with a 30º corrugation angle. The correlation obtained numerically was compared to the one obtained from previous experimental work and they were found to be very similar to the experimental one. The constitutive model, under the assumptions used, was found to be a very good approximation for predicting the convective coefficients of stirred yoghurt during cooling in a plate heat exchanger.